Malformações congênitas e o uso de agrotóxicos em municípios de Mato Grosso, período de 2000 a 2009 - Oliveira, Noemi Pereira de (2012)
Brazil is the world's largest consumer of pesticides, and Mato Grosso state that most of these uses, however, pesticides are risk factors for health and the environment as it exposes workers and the entire population to contamination. Maternal exposure to pesticides in the periconceptional period has been associated with significantly increased risk of congenital malformations. Objectives: To assess the association between the use of pesticides and congenital malformations in selected cities in the State of Mato Grosso in the period 2000 to 2009. Method: We used two types of study: first, an ecological study to select the municipal regions of greater exposure to pesticides according to indicators of exposure. To calculate the scores and ranking of the cities were made the proportions of the amount of pesticides per inhabitant, total tractors per farm worker and farm workers by formal workers. The second this is a population-based study conducted in selected cities. We calculated the exposure levels of the population and bivariate analyzes and logistic regression to measure the association between pesticide exposure and the occurrence of congenital malformations. Results: We selected the municipalities of Campo Novo Parecis, New Mutum, Diamond, Black Stone, Green Field, Lucas do Rio Verde, Sorriso and Primavera do Leste because of those achieving the highest scores for pesticide exposure. There was a statistically significant association between pesticide exposure and congenital malformation in the post-fertilization and the total period. Conclusion: The indicators of exposure to pesticides show consistency, because the municipalities with the highest scores are large agricultural producers and utilizes large amounts of pesticides on their crops. The association between pesticide use and congenital malformation suggests greater attention to public health as well as greater control over application of pesticides.